Identities and security in East Asia - Bessho, Koro.; International Institute for Strategic Studies (Oxford ; New York : Oxford University Press for the International Institute for Strategic Studies, 1999)
Although East Asia has been relatively free from large-scale conflict in the 1990s, the absence of security organisation or even a sense of community within the region has raised doubts about its future security. China and Japan are likely to bear much of the responsibility for maintaining stability, but both countries have been reluctant to adopt a leadership role. South-east Asian states have been willing to take the initiative outside their sub-region, but they possess neither the resources nor the authority to lead the whole of East Asia. In this environment, issues of identity -- shaped by numerous factors, some of them static such as religion and ethnicity, others more complex, such as "national pride" and past history -- can be as crucial as questions of national interest. This paper analyses the ways in which this sense of identity has affected the actions of the key players in East Asia, and assesses the prospects for the region's future security.
Japan: reluctant leader? -- China: future leader? -- The "ASEAN way"? -- The "Asian way"? -- An Asia-Pacific community?
Includes bibliographical references (pages 81-88).
Keywords: ASEAN; ASEAN; Association of Southeast Asian Nations; Association des nations de l'Asie du Sud-Est.; Since 1900; National security -- East Asia; National security -- Southeast Asia; Group identity -- East Asia; South Asian cooperation; 89.90 foreign policy; 2; South Asian cooperation; Group identity; National security; Politics and government; Regionale samenwerking; Political stability -- East Asia; Politics and political science; East Asia -- Politics and government -- 20th century; Southeast Asia -- Politics and government -- 1945-; East Asia -- Politics and government; x; Asie du Sud-Est -- Politique et gouvernement -- 1945-; 2; 2; East Asia; Southeast Asia; Ostasien; Ostasien; Chine -- y; Japon -- y; Political science